Thainess-based English lessons: Reshaping grassroots English education - Kanoksilapatham, Budsaba (Indonesian Journal of Applied Linguistics, 2018)
In Thailand, the question of how to improve the abilities of English language learners without affecting their Thai identity has arisen. This article reports a study that demonstrates that a series of specifically northern Thainess-based instructions for Grade 4 pupils in northern Thailand could not only teach the pupils about their northern Thainess, but also improve their English vocabulary. A set of northern Thainess-based English lessons as well as the corresponding Thainess and English vocabulary pretests and posttests were designed for use in four elementary schools in the north of Thailand. The pretest and posttest scores on both aspects showed that both the pupilsâ€™ appreciation of Thainess and their knowledge of English vocabulary considerably improved. The result suggests the positive effects of this system of learning.Â  From a pedagogical viewpoint, it seems that the use of such materials may well be used to improve and reshape English language education throughout the country.